Simulated descent v dexamethasone in treatment of acute mountain sickness: a randomised trial - Keller, Hans-Rudolf; Maggiorini, Marco; Bärtsch, Peter; Oelz, Oswald (The BMJ, 1995)
Objective: Evaluation and comparison of the therapeutic efficacy of a portable hyperbaric chamber and dexamethasone in the treatment of acute mountain sickness. - Design: Randomised trial during the summer mountaineering season. - Setting: High altitude research laboratory in the Capanna Regina Margherita at 4559m above sea level (Alps Valais). - Subjects: 31 climbers with symptoms of acute mountain sickness randomly assigned to different treatments. - Interventions: One hour of treatment in the hyperbaric chamber at a pressure of 193 mbar or oral administration of 8mg dexamethasone initially, followed by 4 mg after 6 hours. - Main outcome measures: Symptoms of acute mountain sickness (Lake Louise score, clinical score, and AMS-C score) before one and about 11 hours after beginning the different methods of treatment. Permitted intake of mild analgesics before treatment and in the follow up period. - Results: After one hour of treatment compression with 193mbar caused a significantly greater relief of symptoms of acute mountain sickness than dexamethasone (Lake Louise score: mean (SD) -4.6 (1.9) v -2.5 (1.8); clinical score: -4.0 (1.2) v -1.5 (1.4); AMS-C score: -1.24 (0.51) v -0.54 (0.59)). In contrast after about 11 hours subjects treated with dexamethasone suffered from significantly less severe acute mountain sickness than subjects treated with the hyperbaric chamber (-7.0 (3.6) v -1.6 (3.0); -4.1 (1.9) v -1.0 (1.5); -1.78 (0.73) v -0.75 (0.82) respectively). Intake of analgesics was similar in both groups. - Conclusion: Both methods were efficient in treatment of acute mountain sickness. One hour of compression with 193mbar in the hyperbaric chamber, corresponding to a descent of 2250m, led to short term improvement but had no long term beneficial effect. On the other hand, treatment with dexamethasone in an oral dose of 8mg initially followed by 4mg every 6 hours resulted in a longer term clinical improvement. For optimal efficacy the two methods should be combined if descent or evacuation is not possible. - - Key messages Key messagesSimulated descent in a hyperbaric chamber quickly relieves symptoms but the effect is short livedThe drug dexamethasone takes longer to work but the effect is longer lastingA combination of the two methods may be the treatment of choice when the subject cannot be transported to lower altitudes
Gesehen am 29.01.2024